From biology to clinical experience: evolution in the knowledge of neuroendocrine tumours - Emilio Bajetta; Giuseppe Procopio; Sara Pusceddu; Filippo Pietrantonio; Massimo Milione; Marco Maccauro; Elena Verzoni; Valentina Guadalupi; Marco Platania (Frontiers Media S.A., 2011)
Neuroendocrine tumours (NETs) represent a group of neoplasias characterized by significant histopathological and biological heterogeneity. Diagnosis of neuroendocrine tumours relies upon histological examination augmented by newer techniques, such as pet-dotatoc scan. Surgery represents the only curative therapeutic approach. In advanced unresectable disease, medical treatment is the best choice. Somatostatin analogues allow adequate control of the carcinoid syndrome with a low effect on tumour cell growth. Chemotherapy has a good activity only in poor prognosis patients. According to the clinical course of the disease, a multimodal approach could be evaluated in selected cases. New target therapy including multikinase inhibitors, monoclonal antibody and m-tor inhibitors is now under clinical investigation for the treatment of advanced NETs. Preliminary results demonstrated a good activity in terms of disease control rate and tumour shrinkage.